A THE PREACHER AND HIS LANGUAGE - Mustafi, Muhamed (International Scientific Journal Vision, 2019)
The reality of Preacher’s function implies its objective language, and the Preacherwould not be successful succulent not related to its objective purpose as well as the concrete responsibility to society and the environment where it lives, namely to the world to which it is addressed during his language.The Preacher in Islam, during his Da’wah function, lives in a real life and faces objective problems, which must be elaborated and resolved. If there is no correlation between his language and objective reality, it cannot be said that there will be any cruel influence nor can it be discussed for eventual success in his sermons because, in such cases, the man with such responsibility, will be considered as a man dealing with fictitious issues, which are known in the world with the term "Fiction".